Rural-urban disparities in tobacco use among middle aged and elderly Indian adults: a multivariate decomposition analysis - Pritam Halder; Anam Anil Alwani; Baridalyne Nongkynrih; Soumya Chakraborty; Anand Krishnan (BMC Public Health)
Abstract Background Globally, rural areas have a higher prevalence of tobacco consumption compared to urban areas. The reasons for this are poorly known but include individual, demographic, socio-economic, cultural and environmental factors. Among middle aged and elderly individuals in India, we estimated the rural-urban disparities in current smoked and smokeless tobacco use and conducted a decomposition analysis to identify the underlying determinates that contributed to the disparities. Methods Data from Longitudinal Ageing Study in India, wave 1 (2017–18) of adults aged more than 45 years was utilised in this analysis. The weighted prevalence of current tobacco use was estimated. Inequalities in tobacco consumption were disaggregated as per wealth index using the concentration index. Multivariate decomposition analysis was conducted to determine the extent to which different determinants of tobacco use (explanatory variables) contributed to rural-urban disparities in tobacco consumption (outcome variable). p < 0.05 was considered significant. Results The weighted prevalence of smoked tobacco use was 13.10% (95% CI: 9.35-18.05%) across India with a rural-urban absolute difference of 7.32%. The weighted prevalence of smokeless tobacco use was 20.43% (95% CI: 15.75-26.06%) with a rural-urban absolute difference of 10.79%. Smoked and smokeless tobacco consumption was concentrated among the poor with concentration indices of -0.01 and -0.07 respectively. Differences in the distribution of the determinants accounted for 59.36% of the difference in smoked tobacco consumption and 57.82% of the difference in smokeless tobacco consumption in rural and urban areas. For smoked tobacco, differences in educational status (41.30%), gender (7.25%) and caste (6.04%) were key contributors to the difference, while for smokeless tobacco, region of domicile (22.17%), educational status (20.08%) and occupational status (9.28%) contributed the most. Conclusion Tobacco use was found to be more prevalent in rural than urban areas and among the poorer wealth quintiles. Differences in the prevalence of various socio-economic and cultural factors were found to contribute to the rural-urban differences in tobacco consumption.